Appropriate Technology Program of Postharvested Coffee: Production, Marketing, and Coffee Processing Machine Business Unit - Indra Mawardi; Nurdin Nurdin; Zulkarnaini Zulkarnaini (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2019)
The growth of the area of coffee plantations continues to increase every year. Therefore, it needs to be supported by the readiness of postharvest technology that is suitable to produce the quality coffee beans. This activity aims to establish a business unit for the Production Center of Postharvested Coffee Technology (PCPCT). This unit business produces and sells the postharvested coffee machines. The method of implementing the activities starts from the establishment of business unit institutions, provision of raw materials, production processes, and the final product marketing. The results of the activity indicate that PCPCT was successfully formed. Appropriate Technology Program (ATP) has been implemented in such way until producing a mobile coffee bean peeling machine (pulper) system, a coffee ore washing machine, a mobile coffee bean peeling machine system, and a coffee bean sorting machine with a vibration mechanism (huller). The product marketing mechanism runs through media brochures, internet websites, and showrooms in the exhibition venues.